Case report: Chronic Candida albicans meningitis: a rare entity diagnosed by metagenomic next-generation sequencing - Kuenzli, Andrea B.; Müller, Mandy D.; Z`Graggen, Werner J.; Walti, Laura N.; Martin, Yonas; Lazarevic, Vladimir; Schrenzel, Jacques; Oberli, Alexander (Frontiers in Cellular and Infection Microbiology, 2024)
The aetiology of chronic aseptic meningitis is difficult to establish. Candida meningitis in particular is challenging to diagnose, as cerebrospinal fluid (CSF) work-up is poorly sensitive and imaging findings nonspecific. A 35-year-old patient with chronic aseptic meningitis, for which repeated microbiological testing of CSF was unrevealing, was finally diagnosed with Candida albicans (C. albicans) radiculomeningitis using metagenomic next-generation sequencing (mNGS). This report highlights the diagnostic challenges and the difficulties of treating shunt-associated fungal meningitis. In addition, it also affirms mNGS as a potentially effective tool for infectious disease diagnosis, capable of detecting pathogens even in the absence of specific target knowledge.